LEGAL PROTECTION OF MINORITY SHAREHOLDERS INTERESTS IN MERGER ACTIONS - Puspita, Lidya; Gunadi, Ariawan (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
partnership, distinguishing it from other business entities that emphasize personal relationships. This legal framework has made limited liability companies attractive to investors, particularly through strategic actions like mergers, which aim to enhance capital structure, competitiveness, and operational efficiency in a dynamic global economy. However, mergers often raise concerns about the protection of minority shareholders, who face potential marginalization due to the dominance of majority shareholders in decision-making processes. This study evaluates the effectiveness of legal protections for minority shareholders in merger actions under the Company Law, identifies gaps in implementation, and proposes policy recommendations to ensure equitable governance. Employing a normative legal research method, the study analyzes primary legal materials (legislation), secondary materials (scholarly literature), and tertiary sources (legal dictionaries). Findings reveal that while the Company Law provides preventive and repressive protections, such as the right to sell shares at a fair price (Article 62) and mandatory general meeting approvals, practical implementation often fails to address power imbalances. Minority shareholders frequently lack influence, and mechanisms like fair price determination are susceptible to manipulation. The study concludes that stronger oversight, enhanced transparency, and stricter enforcement are essential to safeguard minority shareholders’ rights, ensuring mergers align with principles of fairness and good corporate governance.